Estudo da atividade sísmica em São Caetano-PE em 2007 - Lima Neto, Heleno Carlos (2009)
In this dissertation we studied the seismic activity in the São Caetano county, Pernambuco State, Northeastern Brazil, located near the Pernambuco Lineament. The Pernambuco Lineament is a one of Neoproterozoic continental-scale shear zones that deforms the Borborema province. The seismicity estudied occurred in a NE trending branch of Pernambuco Lineament. The seismic activity in São Caetano started in 2006 and in May 20th, 2006 a 4,0 mb earthquake hit there. This was the largest earthquake ever reported in Pernambuco State. This dissertation is the result of a campaign done in the period from Februay 1th 2007 to July 31 th 2007. In this campaign up to nine three-component digital seismographic stations were deployed and the collected data was used to determine hypocenters and focal mechanism. A total of 214 earthquakes, recorded at least by three stations, were analyzed. To determine hypocenters and time origin the HYPO71 program was used assuming a half-space model with parameters : VP (P-wave velocity) equal to 5.90 km/s and the ratio VP/VS 1.70, where VS is the S-wave velocity. The earthquakes hypocentral distribution was approximately 4 km long and agrees with the NE-SW direction of the Pernambuco Lineamento branch. Hypocentres depth range from 2 to 8 km. The composed focal mechanism was made from a group of 14 selected earthquakes. We try firstly to find the fault plane solution matching the polarity distribution at stations, using the FPFIT program. The result was 43 deg ± 15 deg for strike, 59 deg ± 9 deg for dip and -142 deg ± 15 deg for rake. We also fitted a plane using the hypocentral distribution to obtain the dip and azimuth of the hypocentral distribution. The results obtained by this fit were 58 deg for the azimuth, 55 deg for the dip and -155 deg for rake. This result shows a mechanism of a strike-slip dextral fault with a normal component. This dissertation shows, once more, that there is a good correlation between the seismic activity and geological features in the region near the Pernambuco Lineament and its NE branches